The Concept Of Zikir Al-Muqayyad According To The Sunna Perspective: A Study Of The Case In The Majlis Zikir Of The State Of Nine Tasawuf Thariqa, Malaysia - Mohammad Fahmi Abdul Hamid; Abdul Wasik; Khairul Azhar Meerangani; Ishak Sulaiman (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This study focuses on the practice of zikir in the mode of standing and seating on zikir ceremony of sufi’s tarekat in Negeri Sembilan. The problem began when the allegations arose the practice of dhikr in zikir ceremony is not parallel with the Quran and al-Sunah. Therefore, this study evaluates the method of practicing zikir al-muqayyad practiced in the zikir ceremony in sufi’s centre Negeri Sembilan according to the al-Sunah. Zikir ceremonies in sufi’s centre Negeri Sembilan as the focus of the study on the capacity between inter-states that actively hold zikir ceremonies on a regular basis. This study uses a qualitative methodology that is descriptive analysis through observation methods and interviews with sheikh tarekat in Negeri Sembilan which is used as supporting data. The analytical mechanism for field data uses hadith as the main evidence, supported by the evidence of the Qur'an as well as the debate of scholars to see the parallelism of the practice of zikir al-muqayyad guided by the al-Sunnah. The findings show that there are two methods of zikir al-muqayyad that are practiced, namely setting a certain number and reciting dhikr according to the setting of time. This method of dhikr aims to discipline tarekat practitioners to increase zikr and it is a method that complies with the sunnah of the Prophet SAW and has also been practiced by the Salaf generation.